Boreal soil microbial diversity and seed onion mycorrhizal colonization is unaffected by preceding one season crop cultivation - Pakarinen, Aku; Fritze, Hannu; Timonen, Sari; Kivijärvi, Pirjo; Velmala, Sannakajsa (Elsevier, 2021)
Arbuscular mycorrhizal fungi (AMF) enhance plant phosphorus uptake, increase soil water holding abilities, reduce soil erosion and can protect their hosts from soil-borne pathogens. Hence, AMF play an important part in improving sustainable agricultural practices, and information about the effects of different preceding crop species on the following crop's AMF well-being is crucial for designing crop rotations. We studied onion root and soil microbial diversity and onion root AMF colonization rates after being preceded by three AMF hosting and one non-hosting green manure crop species in a boreal climate organic field. One-season cultivation of different preceding green manure crops did not have a strong effect on AMF colonization or microbial diversity in onion roots nor in the surrounding soil. Onions had high AMF colonization and microbial diversity after all four preceding crops. The overall fungal and bacterial populations of the soil reacted more strongly to seasonal variations than preceding crops. The study suggests that one season is a too short time to influence the AMF community in boreal climate organic fields with conventional tillage. Thus, non-host preceding crops can also be used in rotations, especially together with AMF host crops.
Keywords: mykorritsa; luonnonmukainen viljely; Agricultural soil; Arbuscular mycorrhiza; Bacteria; Cover crop; Fungi; Green manure